Two new species of Nyctotherus (Heterotrichidae: Protozoa) from the cecum of the iguana Ctenosaura pectinata from Islas Marias, Nayarit, México - Tijerina Garza, María de la Paz; Mercado Hernández, Roberto (Revista de Biología Tropical, 1986)
Two new Heterotrichidae species from the caecum of the iguana Ctenosaura pectinata are reported. Nyctotherus earlensis n. sp. is smaller than N. hardwickii, its macronucleus is peripherical and presents cyclosis, the citostome is in the posterior third of the cell. N. jimenezis n. sp. presents a macronudeus that varies from oval to triangular, is in the anterior third of the cell and presents cariophore. It differs from N. sokoloffi in the form of the citopharinx.